AN EXTEND OF THE TYPE OF HANH-BANACH FOR SKEW-SYMMETRIC LINEAR FORMS - Malčeski, Aleksa; Manova-Erakovikj, Vesna (Matematichki Bilten, 2011)
In the paper, an extend of the type of Han-Banah for the 2-skew-symmetric linear forms will be considered.